Antioxidant activities and phenolic contents of the methanol extracts of the stems of Acokanthera oppositifolia and Adenia gummifera - Afolayan Anthony J; Jimoh Florence O; Adedapo Adeolu A; Masika Patrick J (BMC, 2008)
Abstract Background Acokanthera oppositifolia Lam (family: Apocynaceae) is a shrub or small tree with white latex, and the leaves of this plant are used in the form of a snuff to treat headaches and in infusions for abdominal pains and convulsions and septicaemia. Adenia gummifera Harv of the family Passifloraceae is a distinctive woody climber whose infusions are used as emetics and are said to help with some forms of depression. Lipid peroxidation has gained more importance today because of its involvement in pathogenesis of many diseases. Free radicals are the main agents in lipid peroxidation. Antioxidants thus play an important role of protecting the human body against damage by the free radicals. Plants containing phenolic compounds have been reported to possess strong antioxidant properties. Methods The antioxidant activities and phenolic contents of the methanol extracts of the stems of Acokanthera oppositifolia and Adenia gummifera were evaluated using in vitro standard procedures. Spectrophotometry was the basis for the determinations of total phenol, total flavonoids, flavonols, and proanthocyanidins. Tannins, quercetin and catechin equivalents were used for these parameters. The antioxidant activities of the stem extract of Acokanthera oppositifolia were determined by the 2,2'-azinobis-3- ethylbenzothiazoline-6-sulfonic acid (ABTS), 1,1-Diphenyl-2-picrylhydrazyl (DPPH), and ferrous reducing antioxidant property (FRAP) methods. Results The results from this study showed that the antioxidant activities of the stem extract of Acokanthera oppositifolia as determined by the 1,1-Diphenyl-2-picrylhydrazyl (DPPH), and ferrous reducing antioxidant property (FRAP) methods, were higher than that of Adenia gummifera. The levels of total phenols and flavonols for A. oppositifolia were also higher. On the other hand, the stem extract of Adenia gummifera had higher level of total flavonoids and proanthocyanidins than that of Acokanthera oppositifolia. The 2, 2'-azinobis-3- ethylbenzothiazoline-6-sulfonic acid (ABTS) activities of the 2 plant extracts were similar and comparable to that of BHT. Conclusion Thus, the present results indicate clearly that the extracts of Acokanthera oppositifolia and Adenia gummifera possess antioxidant properties and could serve as free radical inhibitors or scavengers, acting possibly as primary antioxidants. This study has to some extent validated the medicinal potential of the stems of Acokanthera oppositifolia and Adenia gummifera.